The courts, the church and the constitution aspects of the disruption of 1843 - Rodger of Earlsferry, Alan, Lord, 1944-2011. (Edinburgh : Edinburgh University Press, 2008)
Commissioned by the Clark Foundation for Legal Education, this book derives from the inaugural Jean Clark Lectures, hosted by the University of Aberdeen in 2007. Across three lectures, Lord Rodger of Earlsferry discusses & analyses the legal & constitutional issues surrounding the Disruption of the Church of Scotland in 1843.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Church of Scotland -- Establishment and disestablishment; Free Church of Scotland -- History -- 19th century; Constitutional law -- Scotland -- History -- 19th century; Ecclesiastical law -- Scotland -- History -- 19th century; Scotland -- Church history -- 19th century; Law